Al-Ālaqah baina Tafsīr Āyāt al-Aḥkām wa al-Fiqh al-Muqāran al-Nasy’ah wa al-Taţawwur - Elhut, Mücahit (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
The Holy Qur’an, being the primary source of legislation in Islamic jurisprudence, has motivated Muslim scholars to dedicate efforts to its study, understanding, and application. Among these scholars are jurists who not only engaged in jurisprudence but also endeavored to systematize the Qur'anic verses containing legal rulings in a unique organizational framework, distinct from traditional jurisprudential writing. Some scholars combined opinions from various schools of thought, employing a comparative jurisprudence approach. This approach is clearly embodied in the works of Al-Qurtubi, who, although he provided a complete exegesis of the Qur'an, distinguished his work by its jurisprudential nature, incorporating the views of scholars from multiple schools of thought. Some scholars focused on a single school, though occasionally referencing others, such as Al-Jassas, who supported his views with evidence. Other works were based on the Shafi’i school, such as "Ahkam al-Qur'an" attributed to Al-Shafi'i or what Al-Kiya al-Harrasi extracted from Shafi'i opinions in verses of legal rulings.When discussing the origins of this field, it is evident that it began with the revelation of the Qur'an, as the Prophet (peace be upon him) was responsible for clarifying its rulings, followed by his companions and their successors, as well as the founders of various legal schools. These founders were not limited to the well-known schools today but included others like Al-Awza'i, Al-Layth, and others whose jurisprudential views on many legal verses must be considered and understood in the context of their development.This research aims to provide a definition of the interpretation of verses of legal rulings in the introduction, including an overview of its origins. The first section reviews the history of these studies, while the second section explains the main methodologies employed in these works and the general characteristics of this type of exegesis. The conclusion presents the key findings and recommendations.